STUDENTS’ LISTENING HABITS TO ENGLISH SONGS AND THEIR VOCABULARY MASTERY - Muntuan, Yeyen Y; Sengkey, Virginia Gabrella (ENGLISH JOURNAL, 2024)
This study aimed to determine the level of students’ listening habits to English songs and their level of vocabulary mastery. In addition, this study also aimed to determine whether there is a significant correlation between students’ listening habits to English songs and their vocabulary mastery. The methods used in this research were descriptive and correlation. The instrument used in this study was a questionnaire adapted from Yi-Chun Chen cited in Setia (2022), and the vocabulary test is adapted from Nation cited in Setia (2022). This research included 63 grades VII, VIII, and IX students at a public junior high school in Minahasa, North Sulawesi. The results showed that the level of students’ listening habits to English songs was 59, which is in the moderate category. Secondly, the students’ vocabulary mastery level was 14.37, which is in the very low category. Lastly, this study showed that there was no significant correlation between students’ listening habits to English songs and their vocabulary mastery. Therefore, further investigation needs to be conducted to identify the variables significantly correlating with the students’ vocabulary mastery.